Subjectivity and difference: Butler and Braidotti - Jagusiak, Agnieszka (Hybris, 2014)
Judith Butler and Rosi Braidotti are recognized as the inheritors of postmodern tradition, in their ideas deconstruct the myth of a stable and an unequivocally characterized identity. Both, Butler and Braidotti express the belief, that human being cannot get rid of defining her/his own subjectivity. Therefore, Braidotti and Butler have created original concepts of the subjectivity. Both, Judith Butler and Rosi Braidotii, represent the third wave of feminism, therefore they begin the discussion on the subjectivity from similar initial assumptions: the end of "I/self" understood in a metaphysical way, the definition of a new subjectivity of women. Judith Butler drawing on J.L. Austin’s philosophical achievements and the theory of performative acts of speech (performative utterance), creates an innovative concept of the subjectivity, which is established by/through performative acts. Rosi Braidotti is focused on the revision of the idea of the woman and the constitution of new women’s subjectivity. Braidotti conceives woman as a nomadic entity, who is ambiguous, embodied, cultural, etc.